Efektivitas Komunikasi Kelompok Pengajian Jemaah Lansia dalam Meningkatkan Pengetahuan Agama di Medan Sekitar Lingkungan Masjid Ar-Razab Deli Serdang - Padang, Salsabila (Asian Journal of Islamic Studies and Da'wah, 2023)
This research aims to find out how the Dai group's communication method is towards the elderly and to determine the effectiveness of the Dai group's communication method towards the elderly in increasing religious knowledge around the Ar-Razab Mosque in Deli Serdang.The type and research approach used is a qualitative method with a descriptive qualitative approach (field research). The data analysis technique used is the descriptive qualitative approach proposed by Sugiyono. Systematics that explain the problem formulation that guides research to explore or photograph social situations that will be studied comprehensively, broadly, in depth and conclusions can be drawn in increasing religious knowledge in the elderly.The research results obtained are on religious knowledge material where this phenomenon is important to be raised as a problem for preachers and the elderly. The understanding of the elderly can be formed properly starting with routine recitation, from here they will be taught moral knowledge about Religion and the Koran by a preacher. Therefore, the role of the preacher is no less important in influencing the elderly or directing the elderly to have an interest in learning about religious understanding with a preacher who is an expert in their field. Because in general the memory of the elderly weakens or declines as they age. If they are not consistent, they will easily forget and not apply the knowledge that has been conveyed.